Improving cost and time control in construction using Building Information Model (BIM): a review - Muhammad, Muhammad Tahir; Haron, Nuzul Azam; Ales @ Alias, Aidi Hizami; Harun, Aizul Nahar; Muhammad, Isa Bala; Baba, Dorothy Ladi (Universiti Putra Malaysia Press, 2018)
The control of cost and time in construction projects is one of the most important issues in construction since the emergence of the construction industry. A successful project should meet not only quality output standards, but also time and budget objectives. The management and control of cost and time in construction is fundamental in every project. An effective cost and time management and control technique for construction projects is important in managing risk of cost overrun and delay in completion of projects. Construction projects are becoming more complex as they now involve many stakeholders from different disciplines. The emergence of Building Information Model (BIM), an alternative technology is believed to solve issues related to project cost and time control as it efficiently increases collaboration between stakeholders. The aim of this paper is to review and summarise the causes of delay and cost overrun in construction industries, which are the main causes of disputes and abandonment of projects in the industry. It was found that delays and cost overrun eat deep into the industry and leave the construction industry with a bad image for decades even with rapid advancement in technology. The review of the applications of BIM showed that most of the applications are geared towards minimising construction cost and time spent on projects. This means that the use of BIM in the management of construction projects has great impact on project cost and time.